Review of Sustainable Productivity of Dryland Farming Systems Through Furrow Diking - Chiroma, A. M.; Kundiri, A. M.; Ibrahim, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
In areas where crop production is limited by low and variable rainfall, the search continues for cultural practices that conserve soil and water while maintaining or improving crop yield and quality. One of such practices is furrow diking (also known as tied-ridging, furrow damming, basin tillage or micro basin tillage). The practice involves constructing small earthen dams or dikes at certain intervals in furrowed fields to capture potential runoff water, thus increasing the ponding period for infiltration. This paper attempts to highlight the potentials of this land configuration practice for improving crop yields in areas where crop production is limited by low and variable rainfall. The constraints associated with its use have been identified and prospects for improving its effectiveness under various climatic conditions are discussed. Cost implications of the practice, as well as suggestions for scaling down costs are considered. Maximum benefits from furrow diking are generally obtained in dryland areas characterized by high intensity, short duration rainfall events which produce significant runoff.